KLASIFIKASI POLI YANG DIBUTUHKAN PASIEN PADA KLINIK BERDASARKAN JENIS PENYAKIT DENGAN MENGGUNAKAN ALGORITMA C4.5 - Danton Ramadhan (2021)
When carrying out treatment activities at the clinic, the patient will consult beforehand regarding the complaints felt with the doctor in charge. During the current pandemic, activities such as talking or chatting are very limited because according to health experts and health ministry regulations one of the causes of transmission of the virus is through throat fluids or saliva. In this case, the consultation requires digitization or modernization by making an application that will determine what type of poly the patient needs. ALODOKTER is an website that contains health information with experts and also includes data regarding diseases and symptoms that can be processed specifically to obtain a classification. Poly classification is carried out based on the symptoms the patient feels where this application acts like a general practitioner who is on guard and conducting surveys or consulting with patients. The symptom data selected by the patient will be processed by the C4.5 Algorithm which will then produce the selected poly output based on the patient's selected symptoms. The C4.5 algorithm is a decision tree algorithm that can perform a classification. This study aims to create an application that can classify the symptoms of patient complaints to determine the appropriate poly. By using a data sample of 12 serious diseases from ALODOKTER, 22 rules are generated from the calculation and making of a decision tree using the C4.5 algorithm with an accuracy of 90.04% using confusion matrix testing with data sharing as much as 70% for training and 30% for testing.